2002
DOI: 10.1055/s-0038-1634316
|View full text |Cite
|
Sign up to set email alerts
|

Person Identification from the EEG using Nonlinear Signal Classification

Abstract: Summary Objectives: This paper focusses on the person identification problem based on features extracted from the ElectroEncephaloGram (EEG). A bilinear rather than a purely linear model is fitted on the EEG signal, prompted by the existence of non-linear components in the EEG signal – a conjecture already investigated in previous research works. The novelty of the present work lies in the comparison between the linear and the bilinear results, obtained from real field EEG data, aiming towards identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The sample size of our study, while small, is comparable to that of other EEG authentication studies (Poulos et al, 2002; Marcel and Millan, 2007; Ashby et al, 2011; Chuang et al, 2013; Curran et al, 2016) and other custom-fit in-ear EEG research (Kidmose et al, 2013; Mikkelsen et al, 2015). The fitting and manufacturing of custom-fit earpieces for each recruited participant was the main limitation to increasing our sample size.…”
Section: Discussion Limitations and Directions For Future Worksupporting
confidence: 74%
See 1 more Smart Citation
“…The sample size of our study, while small, is comparable to that of other EEG authentication studies (Poulos et al, 2002; Marcel and Millan, 2007; Ashby et al, 2011; Chuang et al, 2013; Curran et al, 2016) and other custom-fit in-ear EEG research (Kidmose et al, 2013; Mikkelsen et al, 2015). The fitting and manufacturing of custom-fit earpieces for each recruited participant was the main limitation to increasing our sample size.…”
Section: Discussion Limitations and Directions For Future Worksupporting
confidence: 74%
“…In 2005, Thorpe et al motivated and outlined the design of a passthoughts system (Thorpe et al, 2005). Since 2002, a number of independent groups have achieved 99–100% authentication accuracy for small populations using research-grade and consumer-grade scalp-based EEG systems (Poulos et al, 2002; Marcel and Millan, 2007; Ashby et al, 2011; Chuang et al, 2013). Several recent works on brainwave biometrics have independently demonstrated individuals' EEG permanence over 1–6 months (Armstrong et al, 2015; Maiorana et al, 2016) or even over 1 year (Ruiz-Blondet et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Relevance for individually personal information in EEG signals was revealed in the early 1930s [1]. Even though EEG has low spatial resolution compared to fMRI, several studies have shown considerable accuracy in this domain [2][3][4]. Pozo-Banos et al [5] reported in a comprehensive review about EEG subject identification that EEG has subject-specific information.…”
Section: Related Researchmentioning
confidence: 99%
“…A strong alpha wave is expressed as a low brain behavior index. Stable alpha behavior indicates high brain activity [40]. The beta wave, on the other hand, is associated with the state of thought, which is prominent in frontal cortex and the surrounding area.…”
Section: ) Eeg For Msamentioning
confidence: 99%